Reducing inequities in maternal and child health in rural Guatemala through the CBIO+ approach of Curamericas: 2. Study site, design, and methods - Henry B. Perry; Mario Valdez; Stanley Blanco; Ramiro Llanque; Shayanne Martin; Jason Lambden; Corey Gregg; Kaitlin Leach; Elijah Olivas; Barbara Muffoletto; Jacqueline Wallace; Nina Modanlo; et al. (BMC, 2023)
Abstract Background The Curamericas/Guatemala Maternal and Child Health Project, 2011-2015, included implementation research designed to assess the effectiveness of an approach referred to as CBIO+﻿ , composed of: (1) the Census-Based, Impact-Oriented (CBIO) Approach, (2) the Care Group Approach, and (3) the Community Birthing Center Approach. This is the second paper in a supplement of 10 articles describing the implementation research and its findings. Paper 1 describes CBIO+ , the Project Area, and how the Project was implemented. Objective This paper describes the implementation research design and details of how it was carried out. Methods We reviewed the original implementation research protocol and the methods used for all data collection related to this Project. The protocol and methods used for the implementation research related to this Project were all standard approaches to the monitoring and evaluation of child survival projects as developed by the United States Agency for International Development Child Survival and Health Grants Program (CSHGP) and the CORE Group. They underwent independent peer review supervised by the CSHGP before the implementation research began. Results The study area was divided into two sets of communities with a total population of 98,000 people. Project interventions were implemented in Area A from 2011 until the end of the project in 2015 (44 months) and in Area B from late 2013 until 2015 (20 months). Thus, Area B served as a quasi-comparison area during the first two years of Project implementation. The overarching study question was whether the CBIO+ Approach improved the health and well-being of children and mothers. The outcome indicators included (1) changes in population coverage of evidence-based interventions, (2) changes in childhood nutritional status, (3) changes in the mortality of children and mothers, (4) quality of care provided at Community Birthing Centers, (5) the impact of the Project on women's empowerment and social capital, (6) stakeholder assessment of the effectiveness of the CBIO+ Approach, and (7) the potential of wider adoption of the CBIO+ Approach. Conclusion The implementation research protocol guided the assessment of the effectiveness of the CBIO+ Approach in improving the health and well-being of children, mothers, and their communities.